2017
DOI: 10.7326/m16-2855
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring Versus Usual Care in Patients With Type 2 Diabetes Receiving Multiple Daily Insulin Injections

Abstract: Dexcom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
322
3
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 477 publications
(359 citation statements)
references
References 29 publications
22
322
3
12
Order By: Relevance
“…Use of a CGM or an insulin pump has been shown to improve A1C [3,20,21,22••, 23] and decrease the occurrence of hypoglycemia [24, 25]. The impact of CGM use is undeniable, as demonstrated by a median reduction of 30% in hypoglycemic events in adults who use CGMs compared those who do not [24].…”
Section: Biopsychosocial Factors Associated With Cgm and Insulin Pumpmentioning
confidence: 99%
“…Use of a CGM or an insulin pump has been shown to improve A1C [3,20,21,22••, 23] and decrease the occurrence of hypoglycemia [24, 25]. The impact of CGM use is undeniable, as demonstrated by a median reduction of 30% in hypoglycemic events in adults who use CGMs compared those who do not [24].…”
Section: Biopsychosocial Factors Associated With Cgm and Insulin Pumpmentioning
confidence: 99%
“…The analysis was conducted on a data set with a median of 13 days of CGM measurements plus 39 days of fingerstick blood glucose measurements. To assess the mean glucose–HbA 1c relationship with current CGM technology and a greater amount of data, we pooled data collected in 387 participants (age range 20–78 years, 83% white, 315 with type 1 diabetes and 72 with type 2 diabetes) in three randomized trials using the Dexcom G4 Platinum CGM System with an enhanced algorithm, software 505 (Dexcom, Inc., San Diego, CA) (4,15,16). Mean glucose concentration was determined for each participant using up to 13 weeks of CGM data (median amount of CGM data 66 days) and plotted versus HbA 1c measured following the collection of the CGM data at the Northwest Lipid Research Laboratories, University of Washington, Seattle, WA, using nonporous ion exchange high-performance chromatography (TOSOH, Biosciences, Inc., South San Francisco, CA).…”
Section: Introductionmentioning
confidence: 99%
“…15, 16, and 28 (ClinicalTrials.gov identifiers NCT02282397, NCT02282397, and NCT02258373, respectively).†95% CI for a patient’s mean glucose concentration for a measured HbA 1c level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the use of CGM devices also improves overall glucose control and can lower long‐term hemoglobin A 1c (HbA 1c ) in diabetes mellitus patients through greater glycemic awareness (see reviews6, 7). These findings were recently confirmed in the DIAMOND trial, in which 24 weeks of CGM therapy improved glycemic control in both type 18 and type 29 diabetes mellitus patients on multiple daily insulin injections. Moreover, the American Association of Clinical Endocrinologists recommends CGM for patients at risk of hypoglycemia, T2DM patients with unappreciated hyperglycemia, and individuals using intensive insulin therapy regardless of diabetes type 10, 11.…”
mentioning
confidence: 67%